Foraminiferal ecological zonation along a Brazilian mangrove transect: Diversity, morphotypes and the influence of subaerial exposure time. - Semensatto-Jr, Decio Luis; Funo, Rogerio Hideki Ferreira; Dias-Brito, Dimas; Coelho-Jr, Clemente (Elsevier, 2009)
Two foraminiferal associations comprising only arenaceous species define two distinct environments in a 340 m-long mangrove transect at Cardoso Island, Trapande Bay (Cananeia-Iguape estuarine system, SP, Brazil). The "lower muddy flat" (LMF), from the outer mangrove fringe inwards towards land (100 m), is positioned in the lower plain between 0.04 and 0.23 m above the mean sea level (msl), and remains subaerially exposed between 48.5 and 65.6% of the time. This environment is characterized by higher foraminiferal diversity and evenness (McIntosh's D = 0.54 [plus or minus] 0.21 and Pielou's E = 0.68 [plus or minus] 0.25, respectively) and is dominated by Arenoparrella mexicana and Trochammina inflata, and to a lesser extent by Ammotium directum and Textularia earlandi. The mangrove plant of this segment is a Rhizophoretum with average height of 8.4 [plus or minus] 1.2 m. The sediment is characterized by higher concentration of organic matter (93.5 [plus or minus] 32.3 g dm-3) and metals (e.g. V = 53.4 [plus or minus] 21.8 ppm and Zn = 46.4 [plus or minus] 21.3 ppm). The "upper sandy flat" (USF), 240 m wide along the transect, is positioned in the upper plain between 0.28 and 0.89 m above the msl, and remains subaerially exposed between 69.7 and 98.5% of the time. This environment is characterized by a lower diversity and evenness (D = 0.33 [plus or minus] 0.17 and E = 0.49 [plus or minus] 0.20, respectively). The association is dominated by species T. inflata and Miliammina fusca. The Rhizophoretum exhibits a lower average height of 3.6 [plus or minus] 0.6 m. The sediment is poorer in organic matter (39.3 [plus or minus] 15.0 g dm-3) and metals (e.g. V = 13.0 [plus or minus] 6.8 ppm and Zn = 6.9 [plus or minus] 3.7 ppm). Whereas "elongate" tests (uniserial, biserial and planospiral followed by a uniserial portion) are restricted to the LMF, "spiraled" species dominate the USF. Subaerial exposure time seems to exert a primary influence on species distribution, in addition to salinity and sediment type. Species may be adapted to different exposure times, a factor dependent on their position on the intertidal zone and the tidal regime, which should be taken into account in relative sea level reconstructions based on intertidal foraminifera. These patterns have important implications for studies investigating the ecology and paleoecology of foraminifera and subtle fluctuations in relative sea level during the Quaternary.